PENGARUH DISIPLIN, KOMPENSASI DAN BEBAN KERJA TERHADAP PRESTASI KERJA KARYAWAN PT. MEGA FINANCE CABANG PEKANBARU - Setia Ningsih; Restu '; Ahmad Rifki (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to determine the effect of Discipline, Compensation and Workload Performance Against Employee PT. Mega Finance Branch Pekanbaru. In this study population were all employees totaling 58 people. Given the small number of the population census needs to be done because of the relatively small number of employees, the sampling is done by census sampling technique, in which all employees were targeted sampling. Analysis of data using multiple linear regression with SPSS program. Based on the results of data analysis known that Discipline, compensation and workload simultaneously affect the work performance of employees of PT. Mega Finance Branch Pekanbaru. Discipline partially influence on employee performance PT. Mega Finance Branch Pekanbaru. Compensation partially influence on employee performance PT. Mega Finance Branch Pekanbaru. The workload is partially influence on employee performance PT. Mega Finance Branch Pekanbaru. So expected to company head be can improve employees labour capacity with giving good motivation for example by giving other bonus or appreciation to employees owning contribution more to company, giving heavy sanction to employees which impinge regulation of company so that this matter can improve discipline work employees, giving good and complete facility able to support performance all employees, improving training and education to employees in running its duty, and also entangle all employees in make decision to problems faced by company.Keywords: Discipline, Compensation, Expenses Work And Performance